KESADARAN WAJIB PAJAK MEMEDIASI PENGARUH PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Pada Kantor Pelayanan Pajak Pratama Batu) - Andrianus, Alvin Danniswara (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this study was to determine and analyze theinfluence of knowledge of the tax to the awareness required,influence consciousness taxpayer on tax compliance, influence ofknowledge of tax on tax compliance and awareness taxpayer mediate the effect of knowledge of the tax to compliance of individua taxpayers on the Tax Office Pratama Batu, The study population was individual taxpayers listed in KPP Pratama Batu totaling 20 113 taxpayers and used as a sample of 100 people. The sampling technique in this study using techniques convience sampling (samples based on convenience). The analytical method used in this research is path analysis. Based on the analysis of evidence that knowledge of the tax effect on taxpayer awareness, knowledge of tax effect on tax compliance, awareness taxpayer effect on tax compliance and taxpayer awareness mediates the effect of tax knowledge on tax compliance. The results of this study expected to be used for the evaluation of STO Stone by providing extension to taxpayers about the tax rules that apply so that taxpayers have theawareness and compliance to pay taxes. The researcher can then investigate other factors that affect tax compliance had not studied, such as satisfaction with the service taxation and tax administration system.Keywords: Knowledge, awareness and kepatuhanWajib Taxes